1988
DOI: 10.1227/00006123-198810000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Subtemporal Decompression in Severe Closed Head Injury

Abstract: There is general agreement that aggressive management and monitoring of the patient with closed head injury with control of intracranial pressure (ICP) will improve patient survival and eventual outcome. Conversely, there is little agreement on the value of surgical craniectomy for increasing intracranial volume and subsequently decreasing ICP in these same patients. This study examines 115 patients with severe closed head injuries (Glasgow Coma Score 8 or less) seen at the North Carolina Baptist Hospital betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 5 publications
0
35
0
2
Order By: Relevance
“…The mortality rate in patients treated with barbiturate for raised ICP was extremely high and ranged from 58% to 82%. Gower et al [9] published a rate of 82% and Piek [18] a rate of 58% [18]. Under CPP/ICP monitoring, a widely used adjunctive therapy is controlled hyperventilation.…”
Section: Alternative Therapeutic Modalitiesmentioning
confidence: 99%
“…The mortality rate in patients treated with barbiturate for raised ICP was extremely high and ranged from 58% to 82%. Gower et al [9] published a rate of 82% and Piek [18] a rate of 58% [18]. Under CPP/ICP monitoring, a widely used adjunctive therapy is controlled hyperventilation.…”
Section: Alternative Therapeutic Modalitiesmentioning
confidence: 99%
“…It is estimated that 10-15% of patients admitted with STBI will ultimately manifest medically and surgically intractable elevated ICP with an associated mortality of 84-100% [65,84]. An obvious way to convert the closed box surrounding the brain into an open box is to open the skull by craniectomy, which has been performed for decades [17,23,38,57,61,91].…”
Section: Decompressive Craniectomymentioning
confidence: 99%
“…There is evidence that the operation does favorably influence ICP. In both animal and human studies, surgical decompression has been found to lower ICP by increasing intracranial volume [4,7,25,38,41,42,44,47,54,61,78,89]. Muench et al [81] found that the mean volume gained by surgical decompression ranged from 15.9 to 347.4 cm 3 with a median volume of 73.6 cm 3 .…”
Section: Decompressive Craniectomymentioning
confidence: 99%
See 1 more Smart Citation
“…A report published by Saul and Ducker [9] indicated an 84% death rate when ICP was greater than 25 mmHg despite maximum medical management. Decompressive craniectomy has been proven to reduce ICP that is resistant to maximum medical treatment, improve brain elasticity, improve cerebral perfusion pressure, increase brain tissue PO 2 , and reduce midline shift and brainstem compression, following severe TBI, by increasing intracranial volume [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%